Geogenic controls on the high levels of uranium in alluvial aquifers of the Ganga Basin. (August 2022) - Nizam, Sarwar; Dutta, Subham; Sen, Indra S.
Abstract: The Indo-Gangetic Basin (IGB) alluvial aquifer system provides a reliable drinking water supply to over half a billion people. Understanding the groundwater quality, aquifer processes, groundwater storage, and depletion trends in the IGB alluvial aquifer system— one of the world's most important freshwater resources has been the focus of many previous studies. However, understanding what governs uranium variability in the IGB alluvial aquifer system— for example, whether uranium is released from natural deposits or anthropogenic sources such as mill tailing, emissions from the nuclear industry, combustion of fossil fuels, and phosphate fertilizers— are under-explored but critically important for constraining the environmental fate of uranium. Here, we present surface and groundwater uranium concentration data in the central parts of the IGB alluvial aquifer system. We find a high concentration of groundwater uranium above the World Health Organization provisional guideline value of 30 μg/L in 17% (n = 29) of collected groundwater samples, whereas other heavy metals, namely Cr, Ni, Pb, and Cd were within the recommended range. Trace element systematic demonstrates that anomalous uranium enrichment is primarily derived from geogenic sources, while uranium mobility is predominantly controlled by the alkalinity (a proxy for bicarbonate), hence by soluble uranyl carbonate complexes. As in the year 2020, the Bureau of Indian Standard incorporated uranium as a possible drinking water contaminant, our dataset calls for additional assessments of groundwater uranium concentrations in Indian groundwater resources because uranium concentration data are scarce compared to other geogenic contaminants such as arsenic and fluoride. We conclude that uranium, like arsenic and fluoride, is also critical geogenic contaminant in the alluvial aquifers that needs to be better monitored as higher levels of uranium in drinking water have adverse health effects. Graphical abstract: Image 1 Highlights: Higher levels of groundwater uranium in the Ganga Basin alluvial aquifer system. Uranium is primarily derived from geogenic sources. Bicarbonate complexation controls groundwater uranium enrichment. Heavy metals were within the permissible limits recommended by Bureau of Indian Standards.